Defining and implementing a model for pharmacy resident research projects - Dick TB; Moorman KL; MacDonald EA; Raines AA; Mathews Cox KD (Centro de Investigaciones y Publicaciones Farmaceuticas, 2015)
Objective: To describe a standard approach to provide a support structure for pharmacy resident research that emphasizes self-identification of a residency research project. Methods: A subcommittee of the residency advisory committee was formed at our institution. The committee was initially comprised of 2 clinical pharmacy specialists, 1 drug information pharmacist, and 2 pharmacy administrators. The committee developed research guidelines that are distributed to residents prior to the residency start that detail the research process, important deadlines, and available resources. Instructions for institutional review board (IRB) training and deadlines for various assignments and presentations throughout the residency year are clearly defined. Residents conceive their own research project and emphasis is placed on completing assignments early in the residency year. Results: In the 4 years this research process has been in place, 15 of 16 (94%) residents successfully identified their own research question. All 15 residents submitted a complete research protocol to the IRB by the August deadline. Four residents have presented the results of their research at multi-disciplinary national professional meetings and 1 has published a manuscript. Feedback from outgoing residents has been positive overall and their perceptions of their research projects and the process are positive. Conclusion: Pharmacy residents selecting their own research projects for their residency year is a feasible alternative to assigning or providing lists of research projects from which to select a project.